Functions of Hybrid Media: How Parties and Their Leaders Use Traditional Media in Their Social Media Campaign Communication - Paatelainen, Laura; Kannasto, Elisa; Isotalus, Pekka (Frontiers in Communication, 2022)
Political campaign communication has become increasingly hybrid and the ability to create synergies between older and newer media is now a prerequisite for running a successful campaign. Nevertheless, beyond establishing that parties and individual politicians use social media to gain visibility in traditional media, not much is known about how political actors use the hybrid media system in their campaign communication. At the same time, the personalization of politics, shown to have increased in the media coverage of politics, has gained little attention in the context of today’s hybrid media environment. In this research we analyze aspect of hybrid media campaign communication, political actors’ use of traditional media in their social media campaign communication. Through a quantitative content analysis of the Facebook, Twitter and Instagram posts of Finnish parties and their leaders published during the 2019 Finnish parliamentary elections, we find that much of this hybridized campaign communication was personalized. In addition, we show that parties and their leaders used traditional media for multiple purposes, the most common of which was gaining positive visibility, pointing to strategic considerations. The results have implications for both the scholarship on hybrid media systems and personalization of politics.